From silos to scaffolding: engaging and effective social work practice - Keenan, Elizabeth King; Grady, Melissa D. (Clinical Social Work Journal, 2014)
In this final article of the special issue Beyond the Manual: Using Data and Judgment in Clinical Social Work Practice, we extend the discussion regarding the use of data and judgment. We discuss the multiple sources of data used in practice, including research evidence, client perspectives and experience, moment-by-moment process observation, and client feedback regarding progress towards specific, desired outcomes. We move beyond current debates purporting one framework over another to propose a synthesizing framework that situates evidence-based practice, empirically supported interventions and common elements/mapping and adapting practice within a common factors scaffolding framework. This framework provides a way for social workers to effectively make sound judgments using research and client data within the demands of contemporary practice. The article provides a brief overview of the four practice approaches followed by the proposed scaffolding framework and rationale, and concludes with implications for practice, professional education, and research.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-863-792-919-992 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Common elements; Common factors; Empirically supported interventions; Empirically supported treatments; Evidence-based practice; Research evidence; dept.swk